REPRESENTASI NILAI BUDAYA MAKASSAR DALAM FILM GADIS BULULOE KARYA ARMIN SUPER (Journal of Applied Linguistics and Literature, 2024)
The aim of this research is to describe the cultural values of Makassar in the film Girl Bululce by Armin Super, using cultural theory. In this research using ghaeryası techniques and document studies. The results of this research show that there is a representation of Makassar cultural values in the film Girl Bululoe, namely, pacce cultural values were found in 7 data in the film Girl Bululoe that pacce is a sense of empathy and caring for other humans and easy compassion for humans. Sipakatau cultural values were found in 4 data in the film Girl Bululoe is sipakatau wich means mutual respect, respect and treating all humans well regardless of social status. The cultural value of lambusuk was found in 2 data in the film Girl Bululoe, namely that lambusuk is an attitude of honesty towards oneself, honesty towards humans. Juur towards God Almighty. The cultural value off barani was found in 4 data in the film Girl Bululoe that barani are those who act bravely and heave grat courage. The value of hard work was found 4 data in the film Girls Bululoe, namely reso which means hard work was found 4 data in the film Girls Bululoe, namely reso which means hard work seriously with the aim of achieving a career. Hard work with economic goals, and also education.